MENGGAGAS PEMBIAYAAN PEMBANGUNAN INFRASTRUKTUR DI INDONESIA MELALUI OBLIGASI SYARIAH - Seto, Septian Hario (Jurnal Akuntansi dan Keuangan Indonesia, 2005)
Some of objectives of infrastructure development are pushing economic growth and decreasing unemployment. Economic crises that started in 1997 brought the bad condition in Indonesian infrastructure, this condition arise because government doesn’t have enough fund to increase quality and quantity of the infrastructure. This paper tries to offer new source of fund for Indonesian infrastructure development through Islamic bonds. This is a prospective way to absorb fund, because this type of bonds is very demanding, especially from gulf countries.